Early feeding practices and body mass index z-score among Saudi preschoolers: a cross-sectional study - Rana H. Mosli (BMC, 2022)
Abstract Background: Feeding practices during early years may have long-lasting influences on eating behaviors, growth patterns and body mass index (BMI) trajectory. The objectives of this study were to characterize early feeding practices among mothers in Saudi Arabia and examine their associations with child birthweight and BMI z-score (BMIz) at preschool. Methods: This is a cross-sectional study including 209 mother-child dyads who were recruited from different preschools around the city of Jeddah, Saudi Arabia. Mothers completed the study questionnaire over the telephone and preschoolers' anthropometric measurements were objectively measured using standardized procedures. Primary predictors included variables pertaining to breastfeeding initiation, breastfeeding duration, formula milk introduction, complementary feeding, and offering fruit juice, date syrup-milk mixture, and soda drinks in a baby bottle. The study's primary outcome was BMIz at preschool. Mothers reported child's birthweight and sociodemographic characteristics. Descriptive statistics were used to characterize early feeding practices. Bivariate analyses and linear regression analysis were used to examine the association of early feeding practices with child birthweight and BMIz at preschool. Results: About half of the mothers reported that they have offered fruit juice and/or date syrup-milk mixture in a baby bottle (52.2% and 45.9% respectively), with an average duration of 11.5 months (SD = 7.73) and 5.90 months (SD = 6.13), respectively. Children who were offered fruit juice and/or date syrup-milk mixture in a baby bottle had significantly lower birthweights compared to children who were not (M = 2.79, SD = 0.59 vs. M = 3.06, SD = 0.69, P < 0.01 and M = 2.79, SD = 0.67 vs. M = 3.03, SD = 0.62, P < 0.01, respectively). There was a negative association between introducing fruit juice in a baby bottle and child BMIz at preschool (β: -0.18, 95% confidence interval (CI): -0.83, -0.11); This association was not significant after adjusting for child birthweight and other covariates (β: -0.10, 95% CI: -0.64, 0.09). Conclusion: A large proportion of mothers reported offering fruit juice and date syrup-milk mixture in a baby bottle. Additional research is needed to understand associations with child birthweight and BMIz. Longitudinal and interventions studies can help inform counseling guidelines and community campaigns in order to improve early feeding practices in the region.